Hetero-tri-spin systems: an alternative stairway to the single molecule magnet heaven?. Issue 44 (14th October 2021) - Briganti, Matteo; Totti, Federico; Andruh, Marius
Abstract : Three different spin carriers inside the same molecular system is a promising strategy towards multi-functional magnetic materials. The possible spin topologies have been reviewed and analysed to identify the most promising one. Abstract : The search for molecule-based magnetic materials has stimulated over the years the development of extremely rich coordination chemistry. Various combinations of spin carriers have been investigated and illustrated by a plethora of hetero-spin complexes: 3d-nd, 3d-4f, 2p-3d, and 2p-4f. More recently, two other classes of hetero-spin complexes have grown rapidly: compounds containing three different paramagnetic metal ions, or one radical and two different paramagnetic metal ions (all within the same molecular entity). Such new classes of systems represent a challenge both from a synthetic and theoretical point of view. Indeed, the synthetic control and the understanding of the spin topology effect on the overall magnetic behavior from first-principles is a difficult problem to be solved. The presence of different spin carriers in a single molecule makes such compounds particularly interesting because they offer the possibility of developing new magnetic properties, different from those of hetero-bi-spin or homo-spin systems. A critical overview taking the case of 2p–3d–4f complexes is the focus of this perspective paper. An original organic picture of the state-of-art in this field and new hints about the main directions that should be pursued to achieve hetero-tri-spin systems with large anisotropy barriers, low quantum tunneling of magnetization and, possibly, large blocking temperatures are provided in this article through an analysis based on numerically revisiting already published data and a critical survey of the literature reported so far. The reasons for the limited success obtained for the largely used 3d–2p–4f topology are given along with the ones explaining the failure for the 2p–4f–3d case. The still never synthesized linear 2p–3d–4f spin topology seemed to be the most promising one based on the results obtained for the unique closed hetero-tri-spin closed triangular system synthesized so far.